Advanced information systems engineering workshops : CAiSE 2017 International Workshops, Essen, Germany, June 12-16, 2017, Proceedings /: CAiSE 2017 International Workshops, Essen, Germany, June 12-16, 2017, Proceedings. (2017) - Unknown
No abstract available